Photovoltaic maximum power point tracking under fast varying of solar radiation. (1st October 2016) - Belkaid, A.; Colak, I.; Isik, O.
Highlights: An INC-MPPT technique is improved for PV plant. Dynamic efficiency of the basic INC under a gradual irradiance profile is improved. Energy conversion efficiency is increased by approximately 5%. Stringent irradiance profile with different shapes is selected as in EN50530. A robust tracker is proposed for variable irradiance, temperature and load. Abstract: Perturb and Observe (P&O) and Incremental Conductance (INC) are widely used as Maximum Power Point Tracking (MPPT) techniques in Photovoltaic (PV) systems. But, they fail under rapidly varying of sunlight levels. This paper proposes a new MPPT technique, which can make a distinction between perturbation in the reference voltage and sudden-changing of sunlight and thus optimize the PV system efficiency. This method consists on a modified INC algorithm, which is used to fine-tune the duty cycle of the DC/DC converter in order to avoid divergences of the maximum power point (MPP) when using basic INC under fast varying of luminosity levels. The proposed PV-MPPT system, which is composed by a step-up converter as the interface to feed the load, is tested by simulation within the Matlab/Simulink software by taking into account the luminosity, the temperature and the load variation. The simulation results are satisfactory and demonstrate that the improved INC technique can track the PV maximum power at diverse operating conditions with the most excellent performance, the energy conversion efficiency is increased by approximately 5%.